IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK PADA PUSAT KESEHATAN MASYARAKAT PARIGI KECAMATAN PARIGI KABUPATEN PARIGI MOUTONG - Sufiani, Sufiani (Katalogis, 2018)
In an effort to limit a person's smoking activities in Parigi Moutong District, the Parigi Moutong District Government issued Regulation No. 2 of 2015 by the Regent of Parigi Moutong on Non-Smoking Areas. This study aims to find out how the implementation of the No Smoking Area Policy and the inhibiting aspects of the implementation of the No Smoking Area Policy in the Parigi Health Center. This study uses descriptive qualitative methods and informant selection techniques using purposive sampling technique. The research information was 9 people, the theory used was a model of policy implementation by George C. Edward III (1980). The data in this study were obtained from interviews and documentation. The results of this study indicate that the implementation of the Non-Smoking Area Policy in Parigi Health Center, Parigi Moutong District is still lacking. In the communication aspect there are still people who do not understand the boundaries in the area without smoking area. In terms of resources, the Parigi Community Health Center has a shortage of security personnel and the absence of funds for non-smoking areas. In the disposition aspect, many employees have understood well but there is still an indifferent attitude to reprimand or prohibit smokers who smoke in the community health center. Then, the aspects of Puskesmas Structure Bureaucracy do not yet have a clear SOP regarding smoking bans and the absence of a special team to manage them. The conclusion of this study is that the implementation of the No Smoking Area policy cannot work well due to several inhibiting aspects, namely communication, resources, disposition and the Structure of the Bureaucracy. The advice given is that a special team is needed to be able to control and stop smoking activities. Establish a Standard Operating Procedure (SOP) on the implementation of the Non-Smoking Zone Rules in the Puskesmas Working Area. Cigarettes at Parigi Puskesmas Parigi Moutong district so people can quickly understand about Non-Smoking Areas.